IMPLEMENTASI “SAY NO TO PROMISCUITY”TERHADAP SISWA SMK N 1 SIATAS BARITA UNTUK MENAPAKI MASA DEPAN - Natalia Sianipar; Novianti Kabeakan; Punia L.M Sihombing; Ramayanti Pangaribuan; Damayanti Nababan (Universitas 17 Agustus 1945 Semarang, 2022)
The seminar is aimed at increasing knowledge, insight and awareness of SMK N 1 Siatas Barita students in overcoming promiscuity for the sake of treading the future. The research method used by researchers is to use the action method with a qualitative approach to obtain more detailed information which is focused on the implementation of the seminar which took place at SMK N 1 Siatas Barita which is a form of service to students to avoid promiscuity which is increasingly vulnerable nowadays. The subjects of this study were 91 students of SMK N 1 Siatas Barita, North Tapanuli Regency. This activity was carried out in a day with three sessions in this seminar. This seminar activity is carried out to provide motivation to avoid promiscuity to students who are involved in these activities. The implementation that can be concluded is based on observations made by the seminar implementation team to prevent students from promiscuity, namely by socializing the dangers of promiscuity and providing several methods because this year old students are looking for an identity that allows them to achieve what they want to do. Namely the method used by the seminar implementation team in socializing